2013
DOI: 10.1007/s11655-013-1440-8
|View full text |Cite
|
Sign up to set email alerts
|

Shenfu Injection (参附注射液) suppresses inflammation by targeting haptoglobin and pentraxin 3 in rats with chronic ischemic heart failure

Abstract: SFI could improve hemodynamic function and decrease inflammatory reactions in the pathophysiology of CHF. The serum proteins HP and PTX3 could be potential biomarkers for chronic ischemic heart failure, and they could also be the serum protein targets of SFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…8,9) Appropriate prognostic risk stratification may help clinicians better manage patients by assessing mortality risk. Recent studies have been attempting to identify novel biomarkers such as ubiquitin, Gremlin-1, cyclophilin A, pentraxin-3, and heterogeneous nuclear ribonucleoprotein C. [10][11][12] In our study, we enrolled 287 subjects in order to explore the easily measured and complementary long-term prognostic factors ST2, NT-proBNP, and serum sodium in AHF patients receiving standard treatment according to the guideline. Our goals were to clarify the roles of these 3 variables as indicators of AHF prognosis and to investigate the specific cut-off level for risk stratification.…”
mentioning
confidence: 99%
“…8,9) Appropriate prognostic risk stratification may help clinicians better manage patients by assessing mortality risk. Recent studies have been attempting to identify novel biomarkers such as ubiquitin, Gremlin-1, cyclophilin A, pentraxin-3, and heterogeneous nuclear ribonucleoprotein C. [10][11][12] In our study, we enrolled 287 subjects in order to explore the easily measured and complementary long-term prognostic factors ST2, NT-proBNP, and serum sodium in AHF patients receiving standard treatment according to the guideline. Our goals were to clarify the roles of these 3 variables as indicators of AHF prognosis and to investigate the specific cut-off level for risk stratification.…”
mentioning
confidence: 99%
“…In our study, 12 ml/kg Shenfu injection exerted a cardiotonic effect by dramatically improving myocardial injury to enhance cardiac function and alleviating the occurrence of myocardial hypertrophy and pulmonary congestion; in contrast, 6 ml/kg Shenfu injection had less obvious effects. We subsequently found that Shenfu injection for the treatment of myocardial ischemia in rats was administered at concentrations >6 ml/kg or for periods >7 weeks (Wu et al, 2011; Zheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have demonstrated that Shenfu injection could ameliorate cardiac injury by stabilizing cardiac hemodynamic parameters and improving left ventricular function in IHF (Zheng et al, 2015). Furthermore, using MALDI–MS, Zheng et al (2015) demonstrated that haptoglobin and pentraxin 3 may be inflammatory markers of IHF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al reported that SFI might reduce the expressions of TNF- α and IL-6 in rats with systemic inflammatory response syndrome (SIRS) via inhibiting the activity of NF- κ B [ 10 ]. A very recent study has also proven that SFI could suppress inflammation in rats with CHF [ 11 ].…”
Section: Introductionmentioning
confidence: 99%